2023
DOI: 10.1021/acsami.3c08018
|View full text |Cite
|
Sign up to set email alerts
|

Manganese–Iron Dual Single-Atom Catalyst with Enhanced Nanozyme Activity for Wound and Pustule Disinfection

Ming Zhang,
Wang Xu,
Yumeng Gao
et al.

Abstract: Even though great progress has been achieved in mimicking natural enzyme engineering, few artificial enzymes with efficient catalytic performance and multifunction have been reported. In this study, novel manganese–iron dual single-atom catalysts (Mn/Fe SACs) were synthesized via a hydrothermal/pyrolysis recipe. Iron atoms inside the Mn/Fe SACs adequately exerted the peroxidase (POD)-like activity, its Michaelis–Menten constant, and maximum initial velocity superior to the horseradish peroxidase. Manganese ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“… 40 Zhang et al synthesized novel manganese-iron dual single-atom catalysts (Mn/Fe SACs) to promote wound healing by modulating macrophage polarization into the anti-inflammatory M2 type. 41 Among the diverse nanocatalysts, iron-based biocatalysts have received special attention in diagnosis and disease treatment. 42 Studies have shown that iron-based nanozymes can be used to treat Alzheimer’s disease and cardiovascular diseases, and can also act as anti-inflammatory agents to protect cells from ROS damage.…”
Section: Discussionmentioning
confidence: 99%
“… 40 Zhang et al synthesized novel manganese-iron dual single-atom catalysts (Mn/Fe SACs) to promote wound healing by modulating macrophage polarization into the anti-inflammatory M2 type. 41 Among the diverse nanocatalysts, iron-based biocatalysts have received special attention in diagnosis and disease treatment. 42 Studies have shown that iron-based nanozymes can be used to treat Alzheimer’s disease and cardiovascular diseases, and can also act as anti-inflammatory agents to protect cells from ROS damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, this enzyme activity has recently been shown to also enhance the antimicrobial effect of POD nanozyme. Zhang et al developed a bimetallic single-atom nanozyme (Mn/Fe SACs) through high-temperature pyrolysis, 59 which simultaneously exhibited POD, CAT, and GSH-oxidase-like activities. Under acidic conditions, these Mn/Fe SACs could perform the POD and GSH-oxidase-like catalytic effect to kill bacteria.…”
Section: Improvement Of the Antimicrobial Capacity Of Pod Nanozymesmentioning
confidence: 99%
“…Dual SAzymes are also reported based on the existing SAzyme. Dual-metal atom nanozymes (DAzymes), including two identical or different metal atoms as active centers, represent a significant advancement in the field of catalysis, offering distinct advantages over their single-atom catalyst counterparts. By incorporating a second metal atom, DAzymes effectively overcome some limitations associated with SACs.…”
Section: Metal Atom-based Nanozymes For Treatmentsmentioning
confidence: 99%